Budikdamber: Produktivitas Dari Kampus Upaya Membantu Ekonomi Mahasiswa Politeknik ‘Aisyiyah Di Masa Pandemi Covid-19 - Desi Asmaret; Fitri Yulianis (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic has brought drastic changes to the economic conditions of parents of students who on average work as farmers, traders, and fishermen. It is necessary to find a solution that contributes to overcoming the problem. This community service aims to help students find practical solutions during the Covid-19 Pandemic in meeting their daily needs while boarding in the city of Padang by means of Budikdamber, namely Fish Cultivation in buckets filled with kale plants. The service method that will be carried out is practical training or Participation Action Research service, namely service that requires active participation from the servant. The Budikdamber PAR method is used as a way to help the student's economy so that they are responsible for themselves in maintaining the continuity of their life goals as family members. This budikdamber service is very important to be trained for students as a practical solution in increasing income to help ease the economy of parents, especially to overcome difficulties in paying tuition fees.